TPO signaling: When the tyrosines go marching in(side) - Pozner, Roberto Gabriel (2008)
In this issue of Blood, Hitchcock and colleagues provide novel insights into the molecular pathways regulating TPO-mediated c-Mpl trafficking, highlighting the essential role of AP2 in receptor internalization and lysosomal degradation as new pieces in the TPO/c-Mpl signaling puzzle.